Engineering thermal reservoirs for ultracold dipole–dipole-interacting Rydberg atoms - D W Schönleber; C D B Bentley; A Eisfeld (New Journal of Physics, 2018)
We consider an open quantum system of ultracold Rydberg atoms. The system part consists of resonant dipole–dipole-interacting Rydberg states. The environment part is formed by ‘three-level atoms’: each atom has a ground state, a short-lived excited state, and a Rydberg state that interacts with the system states. The two transitions in the environment atoms are optically driven, and provide control over the environment dynamics. Appropriate choice of the laser parameters allows us to prepare a Boltzmann distribution of the system’s eigenstates. By tuning the laser parameters and system-environment interaction, we can change the temperature associated with this Boltzmann distribution, and also the thermalization dynamics. Our method provides novel opportunities for quantum simulation of thermalization dynamics using ultracold Rydberg atoms.